Design and development EduPocket A+ - Akmar, Norfaridatul; Nadhirah, Nur Yasmin; Tasneem, Ainul; Sabrina, Iman; Nasuha, Fitrah (Universitas PGRI Kanjuruhan Malang, 2021)
The objective of Science, Technology, and Engineering Mathematics (STEM), is not only focused on scientific knowledge and concepts but 21st century skills such as collaborative skills, communication, critical thinking, creativity and computational thinking should be emphasized in science learning. This concept paper discusses how to develop the EduPocket A+ and this application features easy-to-grasp notes and animations to present the Physics syllabus in a simple manner. EduPocket A+ is an (Android APK) application where individuals are able to access notes) through interactive means as well as prep individuals to answer essay questions for the SPM Physics Paper 2. A review of the literature shows that educational games can improve student academic achievement. In addition, this learning approaches provide a fun learning environment, increasing active engagement students in learning, and increase students ’interest and motivation in STEM education. However, studies on game-based learning involving students as educational games designers or inventors are still lacking in Malaysia, especially at the secondary school. Furthermore, relatively little research has focused on the development of Edu-PocketA+ as effectiveness of educational games mastery of 21st century skills in STEM. Therefore, this concept paper discusses the development of EduPocketA+ that involving students in making games in learning, facilitating strategies in physics learning concepts and improve 21st century skills among students.